Kajian tentang Studi Keterbacaan dalam Pengembangan Bahan Ajar Ekologis di Daerah Lahan Basah - Winarti, Atiek; Yamin, Moh.; Sarbaini, Sarbaini (Vidya Karya Jurnal Kependidikan, 2015)
This research has the objective to assess the readability level of valid, practical and effective learning model in building the students ecological consciousness in the area of wetlands, to increase the listening skills and the students concepts mastery on subject matter relating to the social environment and the generic structure of English. This study intends to develop the instructional materials in the form of Student Worksheet (LKS) used to create a society that has a high sensitivity in listening to the destruction of the ecology in wetland areas. The study population was all students in all junior high schools in Banjarmasin. By using purposive sampling, each of the first class of eighth grade students from three schools located in the area around the river, namely SMPN 4, Junior High School SMPN 5 and 17 became the sample. The number of students of SMPN 27 Banjarmasin is 165 from 5 classes , While the number of students of SMPN 5 Banjarmasin is 170 from 5 classes. The number of students for each class is between 33 and 34 students. Similarly, the SMP 17, the number of students for the sample was relatively the same. The results showed that the material Worksheet 1 and Worksheet 2 is considered to fulfill theÂ criteria of material legibility by respondents where they gave positive responses, ranging from the worksheet itself, which includes the presentation of working procedures easy to understand; pictures in worksheet clarify the material; the questions in worksheet are easy to understand; and questions in worksheets guide the students understand the importance of the environment, including the physical form letter corresponding to the font selection and readable; the font size is large enough and clear; and the overall appearance of worksheet is interesting.